Tis/ T1/T2 EVRELERİNDEKİ MİDE KARSİNOMU OLGULARINDA KÜRATİF REZEKSİYON SONUÇLARI - ERSAN, Yılmaz; Doğusoy, Gülen; ERTÜRK, Süphan; UYSAL, Ömer; ÇİÇEK, Yusuf (Cerrahpaşa Medical Journal, 2019)
Background.- Despite recent improvements in the diagnostic accuracy and techniques for early gastric carcinoma, some patients die of a recurrence, even after resection of an early gastric cancer, (EGC). It has been suggested that patients with T2. No carcinoma of the stomach has a comparable survival rate to patients with T1 carcinoma of the stomach. Study design.- Clinicopathologic features and survival rates of 50 patients with Tis/T1/T2 adenocarcinoma of stomach treated between 1989 to 1993 were reviewed. Prognostic significance of the clinicopathologic features in gastric carcinoma with invasion confined to the stomach wall was studied using both a univariate and a multivariate analysis. Results.- Excluding deaths from causes other than recurrence, five-year survival rate for patients with Tis/T1 carcinoma of stomach was 100 percent. Five-year survival rate for patients with T2 carcinoma of the stomach was 68.8 percent. Conclusions.- In patients with gastric carcinoma with invasion confined to the stomach wall, most important prognostic factor was lymph node invasion.